KARAKTERISASI KUTU KEBUL (BEMISIA TABACI) SEBAGAI VEKTOR VIRUS GEMINI DENGAN TEKNIK PCR-RAPD - Sudiono dan Nur Yasin . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2006)
Characterization of whitefly (Bemisia tabaci) as geminivirus vector based on RAPD-PCR. The variation of whitefly was performed by the appearance of population having diferent DNA sequence. PCR-RAPD and dendogram was expected to be used to investigate the variation of whitefly in Sumatera. Morphological observation on the whitefly colleted from field area showed that the geminivirus-transmitting vector was Bemisia tabaci with varied population. Based on PCR-RAPD and dendogram analysis in Sumatera, it was known that Bemicia tabaci had a high variation both intra and inter field area.